Functionalized silanes and electrolyte composition and electrochemical device comprising same

Organosilicon compounds address the instability of current lithium-ion battery electrolytes by enhancing thermal stability and safety, enabling high-voltage operation and increased energy density, suitable for advanced battery applications.

CN119119100APending Publication Date: 2024-12-13SILATRONIX INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410768573.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2014-10-03
Filing Date
2015-10-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Current lithium-ion battery electrolytes are unstable at high temperatures and voltages, leading to rapid deterioration of electrode materials and battery performance, and are a significant source of energy release during failures, hindering the development of advanced batteries for portable products, electric drive vehicles, and utility-scale applications.

Method used

The use of organosilicon (OS) compounds as electrolyte solvents, which are environmentally friendly, non-flammable, and high-temperature resistant, providing improved thermal stability, increased flash point, and voltage stability, and reducing battery failure rates, compatible with existing lithium-based electrochemical systems.

Benefits of technology

OS-based electrolytes enhance thermal stability, safety, and performance of lithium-ion batteries, allowing for the use of high-voltage cathode materials and higher energy density, suitable for large batteries in EDVs and grid storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119100A_ABST
    Figure CN119119100A_ABST
Patent Text Reader

Abstract

Compounds of the structure R4-a-Si-(Sp-Y) a-Zb are described, wherein "a" is an integer from 1 to 4; and'b 'is an integer from 0 to (3 * a). When'b 'is equal to 0, 'Z' does not exist; otherwise "Z" is "R" or formula (II) wherein "R" is each halogen, a C1-6 linear or branched alkyl, alkenyl or alkynyl group, or a C1-6 linear or branched haloalkyl, haloalkenyl or haloalkynyl group; "Sp" are each a C1-15 linear or branched alkylene group or a CMS linear or branched haloalkylene group; and each Y is an organic polar group. Also described are electrolyte compositions containing one or more of these compounds.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the following application: application date October 5, 2015, application number 201580053444.4, invention name “Functionalized silane and electrolyte composition and electrochemical device containing the same”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] Priority is hereby claimed to U.S. Provisional Application No. 62 / 059,663, filed on October 3, 2014, which is incorporated herein.

[0004] background

[0005] The liquid electrolyte in lithium-ion batteries usually contains a lithium salt, usually LiPF, in an organic solvent blend of ethylene carbonate (EC) and one or more co-solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), or ethyl methyl carbonate (EMC). 6 Unfortunately, LiPF 6 It is unstable at above 60°C and at charging voltages exceeding 4.3 volts in these carbonate solvents. Operating lithium-ion batteries at temperatures or pressures above these causes rapid deterioration of electrode materials and battery performance. In addition, current lithium-ion electrolyte solvents exhibit a flash point of about 35°C and are the main source of energy released during extreme lithium-ion battery failures. In view of these significant limitations, current electrolytes hinder the development of advanced lithium-ion batteries for all uses including portable products, electric drive vehicles (EDVs), and utility-scale use. Large lithium-ion batteries also need to significantly reduce battery failure rates to effectively serve applications in EDVs and grid storage.

[0006] Therefore, there is a long-felt and unmet need for improved electrolyte solutions in energy storage devices such as lithium-ion batteries. SUMMARY OF THE INVENTION

[0008] Disclosed herein are organosilicon (OS) compounds useful as electrolyte solvents in electrochemical devices, among other uses.

[0009] In general, OS compounds are environmentally friendly, non-flammable, high temperature resistant materials. These properties make OS materials very suitable for use as electrolyte solvents, adhesives and coatings in energy storage devices. OS-based electrolytes are compatible with all lithium (Li)-based electrochemical systems, including primary and rechargeable batteries (i.e., lithium-ion batteries, Li-air batteries) and capacitors (i.e., super / ultra-capacitors). The method of designing OS-based electrolytes into lithium batteries involves limited changes in battery design, and these electrolytes can be incorporated into production operations using existing manufacturing processes and equipment.

[0010] The OS compounds described herein can be used as liquid electrolyte solvents to replace carbonate-based solvent systems in traditional lithium-ion batteries. The OS-based solvents provide significant improvements in performance and abuse tolerance in Li-ion batteries, including increasing thermal stability to extend life at high temperatures, increasing electrolyte flash point to improve safety, increasing voltage stability to allow the use of high-voltage cathode materials and achieving higher energy density, reducing battery failure rates to be consistent with the requirements of large lithium batteries for EDV and grid storage applications, and being compatible with materials currently used in Li-ion batteries for ease of adoption in current designs. The functionality of double-layer capacitor (EDLC) devices has also been demonstrated in the case of OS-based electrolytes. The OS compounds described herein can be used in OS-based electrolyte blends to meet the requirements of specific applications in industrial, military and consumer product devices.

[0011] Objects and advantages of the compounds and electrolyte formulations will appear more fully from the following detailed description and accompanying drawings.

[0012] Accordingly, this article discloses:

[0013] 1. A compound selected from:

[0014] (R) 4-a ——Si——(Sp——Y)a——Zb (Formula I)

[0015] in:

[0016] "a" is an integer from 1 to 4; "b" is an integer from 0 to (3 xa);

[0017] When "b" = 0, "Z" does not exist, otherwise

[0018] "Z" is selected from "R" and

[0019]

[0020] Wherein "R" is independently selected from halogen;1-6 A straight or branched alkyl, alkenyl or alkynyl group; and C 1-6 a straight-chain or branched haloalkyl, haloalkenyl or haloalkynyl group;

[0021] In formula I and II, "Sp" is independently selected from C 1-15 Straight or branched alkylene and C 1-15 a linear or branched haloalkylene group; and

[0022] "Y" in Formula I is each independently selected from an organic polar group.

[0023] 2. The compound of claim 1, wherein "Y" is each independently an organic polar group selected from the following:

[0024]

[0025] The bent bond represents C 2-6 Alkylene bridging moiety.

[0026] 3. The compound of claim 2, wherein "Y" is each independently an organic polar group selected from the following:

[0027]

[0028] 4. The compound of claim 3, wherein "R" is independently selected from fluorine and C 1-6 a linear or branched fluoroalkyl, fluoroalkenyl or fluoroalkynyl group; and

[0029] In formula I and II, "Sp" is independently selected from C 1-15 A linear or branched fluoroalkylene group.

[0030] 5. The compound of any one of claims 1 to 4, wherein "a" is 1 and "b" is 0-3.

[0031] 6. The compound of claim 5, wherein "b" is 1 and "Z" is "-R".

[0032] 7. The compound of claim 5, wherein at least one "R" is fluorine and "Sp" is each independently selected from C 1-6 Straight chain alkylene and C 1-6 Straight chain fluoroalkylene.

[0033] 8. The compound of any one of claims 1 to 4, wherein "a" is 2 and "b" is 0-6.

[0034] 9. The compound of claim 7, wherein "b" is 1 and "Z" is "R".

[0035] 10. The compound of claim 7, wherein at least one "R" is fluorine and "Sp" is each independently selected from C 1-6 Straight chain alkylene.

[0036] 11. The compound of any one of claims 1 to 4, wherein "a" is 3 and "b" is 0-9.

[0037] 12. The compound of claim 11, wherein "b" is 1 and "Z" is "R".

[0038] 13. The compound of claim 11, wherein at least one "R" is fluorine and "Sp" is each independently selected from C 1-6 Straight chain alkylene.

[0039] 14. The compound of any one of claims 1 to 4, wherein "a" is 4 and "b" is 0-12.

[0040] 15. The compound of claim 14, wherein "b" is 1 and "Z" is "R".

[0041] 16. The compound of claim 14, wherein at least one "R" is fluorine and "Sp" is each independently selected from C 1-6 Straight chain alkylene.

[0042] 17. The compound of any one of claims 1 to 4, wherein at least one "R" is fluoro.

[0043] 18. An electrolyte composition comprising the compound according to any one of claims 1 to 4 and a salt.

[0044] 19. The electrolyte composition of claim 18, wherein the salt is a lithium-containing salt.

[0045] 20. An electrochemical device comprising the electrolyte composition according to claim 18.

[0046] In further defined variations of the compounds, each "Y" is independently an organic polar group selected from:

[0047]

[0048] Additionally, each "Y" may optionally and independently be an organic polar group selected from:

[0049]

[0050] In an alternative variation of the compound, "a" is 1, and "b" is 0-2; optionally "b" is 1 and "Z" is R. In this variation, an optional embodiment is that at least one "R" is fluorine, and "Sp" is each independently selected from a linear or branched alkylene group that may be fluorinated.

[0051] In another alternative variation of the compound, "a" is 2, and "b" is 0-6; optionally, "b" is 1, and "Z" is R. In this variation, an optional embodiment is that at least one "R" is fluorine, and "Sp" is independently selected from C which can be fluorinated. 1-6 A straight chain or branched chain alkylene group.

[0052] In another alternative variation of the compound, "a" is 3, and "b" is 0-9; optionally, "b" is 1, and "Z" is R. In this variation, an optional embodiment is that at least one "R" is fluorine, and "Sp" is independently selected from C 1-6 A straight chain or branched chain alkylene group.

[0053] In another alternative variation of the compound, "a" is 4, "b" is 0-12; optionally, "b" is 1, and "Z" is R. In this variation, an optional embodiment is that at least one "R" is fluorine, and "Sp" is independently selected from C which can be fluorinated. 1-6 A straight chain or branched chain alkylene group.

[0054] Also disclosed herein is an electrolyte composition comprising the compound and salt of the present invention. Lithium-containing salts are preferred. Also disclosed herein is an electrochemical device comprising the electrolyte composition.

[0055] By nature of the subscripts "a" and "b", the following superordinate structures are expressly within the scope of the compounds disclosed and claimed herein:

[0056]

[0057] The various R groups are as defined above for "R"; Sp is as defined above, and Y is as defined above. Preferably, in all variations of the compounds, Y is a coordinating Li + of organic polar groups.

[0058] When the polar group Y has a valence of two (2) or more, it will have more than one substitution site. Thus, there may be more than one silicon atom bonded to Y via a spacer group, as described above in the definition of Z. Thus, the following structure is also explicitly within the scope of the compounds disclosed and claimed herein:

[0059] wait.

[0060] In all variations of the compound, "halogen" includes fluorine, chlorine, bromine and iodine. Fluorine and chlorine are preferred halogen substituents. The term "salt" is used in its conventional chemical sense herein to refer to an ionic compound produced by the neutralization reaction of an acid and a base. As used herein, salts are purposefully and broadly defined to include all salts, including but not limited to sodium salts, lithium salts, magnesium salts, borates, phosphates, and the like. Non-limiting examples include sodium hexafluorophosphate, sodium perchlorate, bis-trifluoromethanesulfonyl imide sodium, magnesium hexafluorophosphate, magnesium perchlorate, bis-trifluoromethanesulfonyl imide magnesium, magnesium tetrafluoroborate, magnesium trifluoromethanesulfonate, tetraethylammonium tetrafluoroborate (TEA-TFB), tetrabutylphosphonium tetrafluoroborate, tetrabutylphosphonium hexafluorophosphate, tetrabutylammonium tetrafluoroborate, tetraethylammonium hexafluorophosphate, tetraethylammonium perchlorate, and tetraethylammonium bis-trifluoromethanesulfonyl imide acid. The term "lithium-containing salt" explicitly includes but is not limited to LiClO 4 , LiBF 4 、LiAsF 6 、LiPF 6 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N、Li(CF 3 SO 2 ) 3 C、LiN(SO 2 C 2 F 5 ) 2 , lithium alkyl fluorophosphate and lithium bis(chelated)borate.

[0061] Also disclosed herein are electrolyte compositions comprising one or more organosilicon compounds as described in the preceding paragraphs. Also disclosed herein are electrochemical devices comprising such electrolyte compositions. The compounds disclosed herein are well suited for use in formulating electrolytes for use in all types of charge storage devices (e.g., batteries, batteries, capacitors, etc.).

[0062] Compared to conventional carbonate solvents, the organosilicon solvent molecules disclosed herein have remarkable and unexpected thermal stability. Even when formulated into solvents containing, for example, LiPF 6 When used in electrolyte compositions containing lithium salts of 20% to 50% MgCl2, the organosilicon solvents also exhibited remarkable resistance to damage during high temperature exposure and operation. As shown in the Examples and Figures, several variants of the organosilicon solvent molecules disclosed herein have been demonstrated to be effective in LiPF 6Thermal stability in the presence of 200 Å and at temperatures up to and exceeding 175°C. These data demonstrate the inherent benefit of silicon as a fundamental stabilizing element within organosilicon molecular design. Variants of the molecules disclosed herein include non-fluorinated, fluorinated, polyfluorinated, multifunctional, and alternating alkyl structures, as well as many different Li + The functional groups include nitriles, carbonates, sulfones, and esters. Both gas phase decomposition and liquid phase decomposition were measured by EI-MS and NMR, respectively, to determine the activity of the organic silicon solvent and 1M LiPF after exposure to 175°C for 60 minutes. 6 Destruction of the salt electrolyte. No significant gas or liquid phase decomposition of the OS solvent was observed.

[0063] The numerical ranges used herein shall include every value and subset of values ​​contained in the range, whether specifically disclosed or not. In addition, these numerical ranges shall be deemed to provide support for claims involving any value or subset of values ​​within the range. For example, the disclosure of 1-10 shall be deemed to support the ranges of 2-8, 3-7, 1-9, 3.6-4.6, 3.5-9.9, etc.

[0064] All references to singular features or limitations of the invention shall include the corresponding plural features or limitations and vice versa unless otherwise stated or clearly implied to the contrary by the context of the reference. The indefinite articles "a" and "an" shall mean "at least one" unless expressly limited to the singular.

[0065] All combinations of method or process steps used herein can be performed in any order unless otherwise stated or clearly implied to the contrary by the context of the referenced combination. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1A The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with LiPF 6 , LiBF 4 or LiTFSI F1S 3 Oxidative stability of MN. Figure 1B Described in Figure 1A A close-up of the same data shown in .

[0068] Figure 2A and Figure 2B The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship between the measurement of LiPF 6 , LiBF 4 or LiTFSI F1S 3Dual test of reduction stability of MN.

[0069] Figure 3A The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1MLiPF 6 F1S 3 MN or F1S 3 Oxidative stability of M2. Figure 3B Described in Figure 3A A close-up of the same data shown in .

[0070] Figure 4 The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1MLiPF 6 F1S 3 MN or F1S 3 Reduction stability of M2.

[0071] Figure 5A and Figure 5B Describes the LiPF 6 F1S 3 Thermal stability of MN. Figure 5A Described in Figure 5B A close-up of the same data shown in .

[0072] Figure 6 Describes the LiPF 6 F1S 3 Thermal stability of M2.

[0073] Figure 7 F1S with LiTFSI described 3 Thermal stability of MN.

[0074] Figure 8 Describes the LiBF 4 F1S 3 Thermal stability of MN.

[0075] Fig. 9 Describes the pure F1S 3 Thermal stability of MN.

[0076] Fig.10 DF1S with 20% EC and VC / LiBOB is described 3 Thermal stability of MN.

[0077] Fig.11Describes the performance of F1S compared to a carbonate control electrolyte when heated with a de-lithiated NCA cathode. 3 Enhanced stability of MN electrolyte.

[0078] Fig.12 The discharge capacity of cells containing various electrolyte solvents at various charge rates at 30°C is described.

[0079] Fig.13 The construction of the test cell is described.

[0080] Fig.14 Describes the Fig.12 Discharge capacity of batteries with the same electrolyte solvent at various charge rates at 55°C is shown in FIG.

[0081] Fig.15 The construction of an EDLC device is described.

[0082] Fig.16 Describes a method containing TEA-BF 4 DF1S 2 Performance of EDLC devices with MN electrolyte.

[0083] Fig.17 Describes a method containing TBP-PF 6 Performance of EDLC devices with various electrolyte solvents.

[0084] Fig.18 The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1MLiPF 6 Or the oxidative stability of 1ND1N of 1M LiTFSI.

[0085] Fig.19 The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1MLiPF 6 Or the reduction stability of 1ND1N of 1M LiTFSI.

[0086] Fig. 20A and Fig. 20B Describes the use of 1ND1N and 1M LiPF 6 Or the current density (mA / cm2) of 1M LiTFSI cycle scan from 0V to 6V and from 6V to 0V 2 ) and voltage (V, relative to Li / Li + ) relationship curve. Fig. 20A The first cycle is described. Fig. 20B The second cycle is described.

[0087] Fig.21A The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1MLiPF 6 F1S 3 Oxidative stability of MN or 1ND1N; Fig.21B Described in Fig.21A A close-up of the same data shown in .

[0088] Fig.22A The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve of F1S with 1MLiTFSI 3 Oxidative stability of MN or 1ND1N. Fig. 22B Described in Fig.22A A close-up of the same data shown in .

[0089] Fig.23 Mass spectrum illustrating the thermal stability of pure 1ND1N.

[0090] Fig.24 To illustrate the LiPF 6 Mass spectrometry of the thermal stability of 1ND1N.

[0091] Fig.25A Describes how Fig.24 Close-up of the mass spectral features at 24-30 m / z is depicted. Fig.25B Describes how Fig.24 Close-up of the mass spectral feature 49-55 m / z is depicted.

[0092] Fig.26 The thermal stability of 1ND1N with LiTFSI, vinylene carbonate (VC), and lithium bis(oxalato)borate (LiBOB) is described.

[0093] Fig. 27 Describes the LiBF 4 The thermal stability of 1ND1N.

[0094] Fig.28 The discharge capacity of cells containing various electrolytes at various charge rates is described.

[0095] Fig.29 The discharge capacity of cells containing various other electrolyte solvents is described, comparing the first cycle to the fiftieth cycle.

[0096] Fig. 30A Describes a method containing 1ND1N-LiPF 6 The discharge capacity of the battery with electrolyte at various charging rates; Fig. 30B The discharge capacity of cells containing 1ND1N-LiTFSI-based electrolytes at various charge rates is described.

[0097] Fig.31 For 1ND1N with peak attribution 1 HN MR spectroscopy (in CDCl 3 middle).

[0098] Fig.32 F1S with peak attribution 3 MN 1 HN MR spectroscopy (in CDCl 3 )middle.

[0099] Fig.33 DF1S with peak attribution 2 MN 1 H-NMR spectrum (in CDCl 3 )middle.

[0100] Fig.34 DF1S with peak attribution 3 MN 1 H-NMR spectrum (in CDCl 3 )middle.

[0101] Fig.35 F1S with peak attribution 3c MN 1 H-NMR spectrum (in CDCl 3 )middle.

[0102] Fig.36 1S with peak attribution 3 MN 1 H-NMR spectrum (in CDCl 3 )middle.

[0103] Fig.37 Describes a 1M LiPF 6 F1S 3 MC, F1S 3c MN and 1S 3 Gas phase decomposition of DN. The figure shows that there is no significant gas phase decomposition up to 175 °C.

[0104] Fig.38 Describes a 1M LiPF6 DF1S 2 MN, TF1S 2 MN and TF1S 3 Gas phase decomposition of MN. The figure shows that there is no significant gas phase decomposition up to 175 °C. DETAILED DESCRIPTION OF THE INVENTION

[0106] Throughout this specification, a number of abbreviations will be used to more easily name the various organosilicon compounds. The following conventions are used:

[0107] The FnSnMN compound has the general formula:

[0108]

[0109] Where R 1 , R 2 and R 3 The same or different and independently selected from C 1 -C 6 A linear or branched alkyl, alkenyl, alkynyl or halogen (preferably F), and the "spacer" is C 1 -C 6 Straight or branched alkylene (preferably C 1 -C 6 A linear divalent alkylene group), and Y is a polar organic moiety as previously described.

[0110] The compounds disclosed herein can be prepared by many different routes. The general method that can be used to make the compounds is as follows:

[0111]

[0112] R 1 , R 2 and R 3 The group is as defined herein for R; R 4 Has the same definition as Y; "n" is a positive integer.

[0113] The compounds disclosed herein can also be prepared by the following method:

[0114]

[0115] Likewise, R 1 , R 2 and R 3 The group is as defined herein for R; R 4 Has the same definition as Y.

[0116] The compounds disclosed herein are also prepared by a number of specific routes including the following reaction schemes:

[0117]

[0118]

[0119] LiTFSI, bis(trifluoromethane)sulfonyl imide lithium salt (Sigma-Aldrich catalog number 449504), is a commercial product supplied by several international suppliers:

[0120]

[0121] The elements and method steps described herein may be used in any combination whether explicitly described or not.

[0122] All combinations of method steps used herein can be performed in any order unless otherwise specified or clearly implied to the contrary by the context of the recited combination.

[0123] As used herein, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise.

[0124] All patents, patent publications, and peer-reviewed publications (i.e., "references") cited herein are expressly incorporated by reference to the same extent as if each individual reference was specifically and individually indicated to be incorporated by reference. In the event of a conflict between the present disclosure and an incorporated reference, the present disclosure controls.

[0125] It is to be understood that the compounds and compositions disclosed herein are not limited to the particular construction and arrangement of parts illustrated and described herein but include modifications thereof falling within the scope of the claims.

[0126] The compounds disclosed herein are organosilicon compounds having common structural features in the form of one or more terminal or internal polar organic substituents or moieties. As used herein, the terms "polar organic substituent" and "polar organic moiety" are used interchangeably. The terms expressly include, but are not limited to, the following functional groups:

[0127]

[0128]

[0129] Preferred compounds include the following structures, etc.:

[0130]

[0131] The above structures are all described as having terminal cyano groups. This is for the purpose of simplicity only. Similar compounds having internal and / or terminal polar moieties as described above replacing the cyano moiety are clearly within the scope of the present disclosure. Similarly, halogenated compounds are described above as fluorinated compounds. Similar compounds having other halogen substituents (chlorine, bromine and / or iodine) replacing fluorine atoms are clearly within the scope of the present disclosure. For each compound listed, two alternative systematic names are provided (the first designated basic core in each pair of names is nitrile; the second designated basic core is silane.) In addition, a shorthand name for each compound is given, where DF = difluoro, TF = trifluoro, "Sn" represents an alkylene spacer between the silicon atom and the terminal cyanate, isocyanate or thiocyanate moiety, and "n" represents the number of carbon atoms in the spacer. The physical properties of the selected organosilicon (OS) compounds are provided in Table 1.

[0132] Can be named 1NMS, F1S 3 MS and DF1S 3 The following illustrative synthesis of compounds of MS completes the synthesis of analogous sulfones. Note that other sulfones falling within the broader disclosure contained herein can be prepared by the same route by simply changing the starting reagents accordingly.

[0133] The synthesis of 1NMS was carried out as follows: 2-(methylsulfonyl)ethanol was reacted with 0.5 molar equivalent of hexamethyldisilazane and about 1% molar equivalent of Al(H 2 PO 4 ) 3 Mix without solvent. Keep the mixture at about 80°C overnight and distill twice to obtain pure 1NMS.

[0134]

[0135] F1S 3 The synthesis of MS was carried out as follows: allyl methyl sulfide was dissolved in ethanol and mixed with 4 molar equivalents of H 2 O 2 Mix. Add about 3% molar equivalent of ammonium heptamolybdate as an oxidation catalyst. The next day, the solution was treated with NaHCO 3 The solution was neutralized with CH 2 Cl 2 Extract, discard the water portion, and evaporate the organic layer and distill to produce allyl methyl sulfone. Allyl methyl sulfone is hydrosilylated with dimethylchlorosilane using Karstedt's catalyst. The product is fluorinated with NaFHF at about 150°C, filtered, distilled twice, and dried over molecular sieves to produce pure F1S 3 MS.

[0136]

[0137] DF1S 3 The synthesis of MS was carried out as follows: 3-mercaptopropylmethyldimethoxysilane was dissolved in ethanol and mixed with one (1) molar equivalent of NaOH in water. One (1) molar equivalent of Me 2 SO 4 The crude product was treated with 4 molar equivalents of H 2 O 2 The solvent was evaporated and 2 molar equivalents of HF in water were added. The product was oxidized with CH 2 Cl 2 Extraction and distillation.

[0138]

[0139] Additional characterization data for these sulfone compounds is contained in the appendix attached hereto and incorporated herein.

[0140] The reduced viscosity, higher conductivity and reduced flash point with added fluorine and reduced spacer length are shown in Table 1. DF1S 2 MN has the lowest viscosity and the highest conductivity.

[0141]

[0142] Code:

[0143]

[0144] Pure 1ND2, 1ND1, 1ND1N, F1S 3 MN、DPF1S 3 MN、F1S 3 MC, F1S 3 ME, F1S 3 MA, F1S 3 MS, 1NMS, F1S 3 M2 and F1S 3c The physical properties of MN and the electrolyte solutions containing these solvents are shown in Table 2:

[0145] Table 2: Physical properties of solvents and electrolytes

[0146]

[0147] Code:

[0148]

[0149] In addition to the organosilicon compounds disclosed herein, the electrolyte composition of the present invention may also include conventional non-silicon co-solvents. For example, the electrolyte composition of the present invention may include nitrile and carbonate, such as acetonitrile, ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC). The electrolyte composition of the present invention may include a wide range of concentrations (including but not limited to about 1 wt %-about 40 wt %) of non-silicon co-solvents. Examples of suitable co-solvent concentrations include about 1 wt %, about 5 wt %, about 10 wt %, about 15 wt %, about 20 wt %, about 25 wt %, about 30 wt %, about 40 wt % or between and including any of the aforementioned ranges. Example

[0150] F1S 3 Synthesis of MN:

[0151] Scheme 1 describes the F1S 3 Synthesis process of MN. [F] represents a fluorinating agent, such as HF, NH 4 FHF or other fluorinating agents. NH 4 FHF is preferably used as the fluorinating agent for laboratory scale synthesis. If HF is used, the only by-product is HCl. 3 The MN compound was washed from the solid salt with hexane, distilled, dried with CaO, and distilled again.

[0152]

[0153] Scheme 2 describes the use of NH 4 F1S with FHF as fluorinating agent 3 Synthesis of MN. Using Custer's catalyst (platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution, catalog number 479519, Sigma-Aldrich, St. Louis, MO), approximately 3% substitution occurred on the secondary carbon to produce isoF1S 3 MN. isoF1S 3 MN has a higher 3 MN has a low boiling point and most of it can be separated by fractional distillation.

[0154]

[0155] Scheme 3 describes the use of Cl1S 3 F1S of MN intermediate 3 An alternative shorter synthetic route for MN. 3MN intermediate is available from Gelest, Inc. (Product Code SIC2452.0, 11 East Steel Road, Morrisville, PA). 3 The MN intermediate reduces the time spent during synthesis.

[0156]

[0157] Scheme 4 describes the F1S 3 Another synthetic process of MN. As in process 1, [F] represents a fluorinating agent, such as HF, NH 4 FHF or other fluorinating agents. Using HF as a fluorinating agent in this synthetic process does not produce solid byproducts, so hexane extraction and filtering of solids are not required. The only byproduct is HCl.

[0158]

[0159] Scheme 5 describes the F1S 3 Another synthetic process of MN. As in process 1, [F] represents a fluorinating agent, such as HF, NH 4 FHF or other fluorinating agents.

[0160]

[0161] F1S 3 Synthesis of MN:

[0162] In a preferred route, allyl cyanide is heated to about 100°C using a small amount of Custer's catalyst. Dimethylchlorosilane is added dropwise and refluxed for 4 hours. After cooling to room temperature, the mixture is fluorinated using 1 molar equivalent of ammonium bifluoride at room temperature. Cold hexane is added to the mixture, the solid is filtered off, and the solvent is evaporated. Calcium oxide is added to the crude product and it is vacuum distilled at 45-55°C and 0.4 torr to produce the desired product F1S 3 MN.

[0163] F1S 3 Synthesis of ME

[0164]

[0165] In a preferred route, allyl acetate is mixed with dimethylsilyl chloride and a small amount of Custer's catalyst is added. The mixture is allowed to react overnight. The next day, the mixture is fluorinated overnight at room temperature using 0.33 molar equivalents of antimony trifluoride under vigorous stirring. The next day, the solid is filtered off and the product is vacuum distilled at 25-30°C at 0.3 torr to produce the desired product F1S 3 ME.

[0166] The ester is suitable as an electrochemical solvent in an electrolyte composition. 3 ME vs 1M LiPF 6 It has good solubility and dissolves easily at room temperature. Its flash point of 66°C is acceptable, as is its dielectric constant (Diel.) of 6.6. Its CV oxidation / reduction behavior is also suitable for lithium-ion charge storage cells. Using 80% F1S 3 The full cell cycling of ME electrolyte is stable with good capacity. It maintains very low current density at potentials at or below 5 V at 30 °C. 3 ME is electrochemically feasible via basic Pt oxidation and graphite reduction. It exhibits normal reduction behavior in the first cycle, and passivation is observed in the second cycle. 3 The ME cycled well in the 80% electrolyte formulation in the NMC / graphite electrode system through 26 cycles (data not shown).

[0167] DF1S 3 Synthesis of DN:

[0168]

[0169] Bis(cyanopropyl)dichlorosilane was mixed with 2 molar equivalents of HF aqueous solution at room temperature and the reaction was kept overnight. The crude product was extracted with dichloromethane, the solvent was evaporated, and the product was vacuum distilled at 165°C at 0.1 Torr to give the desired product DF1S 3 DN.

[0170] 1S 3 Synthesis of DN:

[0171]

[0172] DF1S 3 DN was dissolved in THF and cooled with an ice bath, followed by the addition of 2 molar equivalents of methylmagnesium bromide, and the mixture was kept reacting until it slowly reached room temperature. The mixture was quenched with ethanol, the crude product was extracted with dichloromethane, the solvent was evaporated, and the product was vacuum distilled at 125°C at 0.2 torr to yield the desired product 1S 3 DN.

[0173] TF1S 3 Synthesis of MN:

[0174]

[0175] Cyanopropyltrichlorosilane was cooled in an ice bath and 4 molar equivalents of aqueous HF solution were added dropwise. The mixture was kept to react for no more than 2 hours. The crude product was extracted with dichloromethane, the solvent was evaporated, and the product was vacuum distilled at 25°C at 0.2 torr to yield the desired product TF1S 3 MN.

[0176] DPF1S 3 Synthesis of MN:

[0177]

[0178] Dissolve bis(isopropyl)cyanopropylsilyl chloride in THF and cool in an ice bath, then add 1 molar equivalent of HF aqueous solution dropwise and keep at room temperature to react overnight. The next day, evaporate the solvent and distill the product in vacuum at 60° C. at 0.2 torr to produce the desired product DPF1S 3 MN.

[0179] Preparation of DPF1S 3 MN to explore how the larger alkyl group on the silicon atom affects the physical and electronic properties of the molecule. 6 It has good solubility and dissolves easily at room temperature. It exhibits stable oxidation behavior in cyclic voltammetry (CV) up to about 5V. Its CV reduction behavior is also good, and it is passivated in the second cycle. This compound is suitable for electrochemical applications at high temperatures (flash point = 118°C) and at potentials up to about 5V. DPF1S 3 MNs are electrochemically feasible via basic Pt oxidation and graphite reduction.

[0180] DF1S 3 Synthesis of MSO:

[0181]

[0182] According to the mentioned procedure, in DF1S 3 DF1S is obtained as a byproduct of incomplete oxidation during the synthesis of MS 3 MSO.DF1S 3 MSO was purified by vacuum distillation at 40 °C at 0.1 Torr.

[0183] F1S 3 Synthesis of MA:

[0184]

[0185] In this synthesis, 2 molar equivalents of dimethylallylamine were mixed with 1,1,3,3-tetramethyldisiloxane and a small amount of Custer's catalyst. The mixture was heated to 100°C and kept reacting overnight. The next day, the mixture was fluorinated at 150°C overnight with vigorous stirring using 0.67 molar equivalents of antimony trifluoride. The next day, the solid was filtered off and the product was vacuum distilled at 20-25°C at 0.2 Torr to produce the desired product F1S 3 MA.

[0186] F1S 3 Synthesis of MC:

[0187]

[0188] Allyl alcohol was silylated with hexamethyldisilazane using a catalytic amount of aluminum dihydrogen phosphate at 80°C overnight. Prior to the hydrosilylation, the intermediate allyloxytrimethylsilane was distilled to purify it. The hydrosilylation was carried out overnight at 80°C using 1 molar equivalent of dimethylchlorosilane and a small amount of Custer's catalyst. The next day, the mixture was fluorinated and hydrolyzed using 2 molar equivalents of aqueous hydrofluoric acid at room temperature under vigorous stirring to give (3-hydroxypropyl)dimethylfluorosilane, which was distilled before the next step. The final intermediate was dissolved in hexane, 1 molar equivalent of trimethylamine was added, the mixture was cooled in an ice bath, and methyl chloroformate was added dropwise to the mixture, which was then left to react overnight at room temperature. The next day, the solid was filtered off, the solvent was evaporated, and the product was vacuum distilled at 28°C at 0.2 torr to produce the desired product F1S 3 MC.

[0189] Synthetic F1S 3 MC to compare the electrochemical performance of commonly used carbonates with silyl analogs. 3 The CV oxidation and reduction of MC is suitable for electrochemical applications. The synthesis is very good and produces F1S with purity >99.8% 3 MC.F1S 3 MC is easily dissolved in 1M LiPF at room temperature. 6 It shows acceptable cycling and good capacity at 30°C. F1S 3 MC also exhibited good oxidation stability at potentials up to about 5 V. In the CV, the reduction showed two peaks (at 1.7 V and 0.6 V) in the first cycle and showed passivation in the second cycle.

[0190] Determination of electrochemical stability of silicone materials:

[0191] Computational chemistry methods were used to calculate the electrochemical properties of various organosilicon molecules. We performed density functional theory (DFT) molecular orbital calculations using the GAMESS program developed by the Gordon research group at Iowa State University. The HOMO (highest occupied molecular orbital) energy levels and LUMO (lowest unoccupied molecular orbital) energy levels associated with the reduction and oxidation potentials of the compounds were calculated at the B3LYP / DZV level. The oxidative stability of electrolytes containing organosilicon solvents was determined in a 3-electrode cell using linear sweep voltammetry (LSV) or cyclic voltammetry (CV). A platinum microelectrode was used as the working electrode, and lithium metal was used as the counter electrode and reference electrode. At a scan rate of 10 mV / s, the potential of the system was increased from the open circuit voltage (OCV) to 6 or 8 V (vs. Li / Li + The resulting current density (mA / cm2) was recorded at each potential. 2 ), higher currents indicate oxidation reactions (i.e., lower oxidation stability). For linear sweep voltammetry, 8V was used as the final potential to evaluate the basic oxidation stability of the material over a wider voltage range. For cyclic voltammetry, 6V was used to evaluate the material in multiple scans at potentials more relevant to traditional battery applications. Multiple scans were performed in cyclic voltammetry experiments to determine the reversibility / irreversibility of any reactions observed.

[0192] The reduction stability of electrolytes containing organosilicon solvents was determined using linear sweep voltammetry (LSV) in a 3-electrode cell. A glassy carbon electrode was used as the working electrode and lithium metal was used as the counter and reference electrodes. At a scan rate of 10 mV / s, the potential of the system was reduced from the open circuit voltage (OCV, typically 3 V) to 0.1 V (vs. Li / Li + The resulting current density (mA / cm2) was recorded at each potential. 2 ), with larger currents indicating reduction reactions (ie, lower reduction stability). Two scans were performed to assess whether the reduction process was reversible or irreversible (ie, passivation).

[0193] F1S 3 Electrochemical stability of MN:

[0194] F1S 3 MN and F1S 3 The molecular orbital diagram of M2 (not shown) reveals that F1S 3 MN (9.07eV) is better than F1S 3 M2 (8.20eV) is larger. F1S 3 MN also has more 3M2 (-6.84 eV) has a higher oxidation potential (-8.75 eV).

[0195] Figure 1A and Figure 1B The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with LiPF 6 , LiBF 4 or LiTFSI F1S 3 Oxidative stability of MN. Oxidative stability at room temperature with Pt as working electrode, Li as counter electrode, Li / Li + The test was performed with a scan rate of 10 mV / s as a reference electrode. Figure 1B Described in Figure 1A A close-up of the same data shown in F1S 3 MN-LiPF 6 The electrolyte exhibited the best oxidative stability with 1 mA / cm at 7.3 V. 2 The current density of F1S 3 MN-LiBF 4 and F1S 3 MN-LiTFSI has 1 mA / cm at 6.8 V and 6.2 V, respectively. 2 of current density.

[0196] Figure 2A and Figure 2B The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with LiPF 6 , LiBF 4 or LiTFSI F1S 3 Reduction stability of MN. Reduction stability at room temperature with Pt as working electrode, Li as counter electrode, Li / Li + The test was performed with a scan rate of 10 mV / s as a reference electrode. Figure 2A and Figure 2B Two separate scans. 3 MN-LiPF 6 The electrolyte showed the best reduction stability.

[0197] Figure 3A and Figure 3B The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1M LiPF 6 F1S3 MN or F1S 3 Oxidative stability of M2. Oxidative stability at room temperature with Pt as working electrode, Li as counter electrode, Li / Li + The test was performed with a scan rate of 10 mV / s as the reference electrode. Figure 3B Described in Figure 3A A close-up of the same data shown in F1S 3 MN confirmed that relative to F1S 3 M2 Improved oxidation stability.

[0198] Figure 4 The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with LiPF 6 Compared with the carbonate control electrolyte, the electrolyte with 1M LiPF 6 F1S 3 MN or F1S 3 Reduction stability of M2. Reduction stability at room temperature with Pt as working electrode, Li as counter electrode, Li / Li + As a reference electrode and the scan rate was 10mV / s. 3 Compared with M2, F1S 3 MN demonstrated lower reduction resistance.

[0199] Determination of thermal stability of pure solvents and formulated electrolytes:

[0200] The thermal stability of both the pure silicone solvent and the electrolyte composition is determined as follows: about 0.75 mL of the liquid sample is heated in a sealed chamber under an argon purge. The argon purge is carried out to an atmospheric sampling mass spectrometer, in which electron impact mass spectrometry (EI-MS) can be used to detect any gas phase impurities and / or decomposition products at very low levels. The sample is kept at a predetermined temperature level (30, 55, 70, 100, 125, 150, 175 and 200°C) related to battery applications for 1 hour. The gas phase decomposition products are identified by comparing the fragmentation pattern obtained from the EI-MS with the NIST standard. After the heating experiment (and detection / collection of all gas phase products), the remaining liquid sample is analyzed via NMR spectroscopy to quantitatively analyze the degree of decomposition. Multiple cores are checked to comprehensively analyze all components of the system, including the silicone solvent, any carbonate co-solvent, all additives and lithium salts (if present).

[0201] F1S 3 Thermal stability of MN:

[0202] Figure 5A and Figure 5B Describes the LiPF 6 F1S 3 Thermal stability of MN. 3 MN-LiPF 6 The electrolyte (Batch ZP815-01) was exposed to temperatures ranging from 30°C to 175°C and analyzed for gaseous and liquid decomposition products by electron impact mass spectrometry (EI-MS) and nuclear magnetic resonance spectroscopy (NMR), respectively. The temperatures at which prominent peaks appeared are noted. 3 MN shows no significant gas and / or liquid phase decomposition up to 175 °C. 2 SiF 2 At 100-125°C, it appears at 81 m / z, and MeSiF 3 At 85 m / z, the peak appears at 150-175°C. However, the 81 m / z peak and the 85 m / z peak appear inconsistently at 100-175°C. In addition, 1 H NMR analysis showed no decomposition after heating to 175 °C. 3 MN showed no consistent decomposition up to 175 °C. Figure 5A Described in Figure 5B Close-up of the same data shown in .

[0203] Figure 6 Describes the LiPF 6 F1S 3 Thermal stability of M2. 3 M2-LiPF 6 The electrolyte was exposed to temperatures between 30°C and 150°C and the decomposition products were analyzed by mass spectrometry. The temperatures at which prominent peaks appeared are noted. 3 M2 shows decomposition at temperatures ≥125°C. Decomposition products include Me 2 SiF 2 and 1,4-dioxane. 1 H NMR analysis showed about 6% decomposition at 150 °C. These results are consistent with those reported for Figure 5A , Figure 5B The results discussed above are combined to show that F1S 3 MN vs F1S 3 M2 is more thermally stable.

[0204] Figure 7 F1S with LiTFSI described 3 Thermal stability of MN. 3MN-LiTFSI electrolyte was exposed to temperatures between 30°C and 185°C, and the decomposition products were analyzed by mass spectrometry. The temperatures at which prominent peaks appeared are noted. Gas phase peaks were observed at temperatures ≥150°C. For F1S 3 MN-LiBF 4 Peaks matching the patterns at 117 and 102 were observed for the electrolyte and pure solvent (see Figure 8 and Fig. 9 ).

[0205] Figure 8 Describes the LiBF 4 F1S 3 Thermal stability of MN. 3 MN-LiBF 4 The electrolytes were exposed to temperatures between 30°C and 200°C and the decomposition products were analyzed by mass spectrometry. The temperatures at which prominent peaks appeared are noted. Gas phase peaks were observed at temperatures ≥ 175°C. For pure solvents and F1S 3 Peaks at 117 and 102 matching patterns were observed for the MN-LiTFSI electrolyte (see Figure 7 and Fig. 9 ). 1 H NMR analysis showed no fluorinated decomposition products and <0.5% of non-fluorinated hydrolysis products.

[0206] Fig. 9 Describes the pure F1S 3 Thermal stability of MN. 3 MN electrolyte was exposed to temperatures between 30°C and 195°C and the decomposition products were analyzed by mass spectrometry. The temperatures at which prominent peaks appeared are noted. Gas phase peaks were observed at temperatures ≥150°C. At 150°C, Me 2 SiF 2 (96 / 81 m / z), but the other peaks were not related to this product. 1 H NMR analysis showed no fluorinated decomposition products and <0.5% hydrolysis.

[0207] The above data show that in the presence of LiPF 6 In the case of F1S 3 MN is the most thermally stable OS solvent.

[0208] DF1S 3 Synthesis of MN:

[0209]

[0210] Commercially available 3-cyanopropyldichloromethylsilane (CAS No. 1190-16-5; Sigma Aldrich, St. Louis, MO, US) was fluorinated with ammonium difluoride at room temperature. Cold hexane was then added to the mixture. The solid was filtered off and the solvent was evaporated. Calcium oxide was added to the crude product. The solvent was vacuum distilled at 35-45° C. and 0.4 torr to produce the desired product in very high purity (about 99.8%) and in about 90% yield.

[0211] DF1S 2 Synthesis of MN:

[0212]

[0213] Acrylonitrile was mixed with N,N,N',N'-tetramethylethylenediamine and copper(I) oxide in a flask and heated to 60°C. Dichloromethylsilane was then added dropwise and refluxed overnight. After cooling to room temperature, the mixture was vacuum distilled (43°C, 0.2 Torr) to produce the dichloro intermediate (DCl1S 2 MN). The intermediate is fluorinated using 1.2 molar equivalents of ammonium bifluoride at room temperature or 1.2 molar equivalents of sodium bifluoride at 130°C. Dichloromethane is then added and the solid is filtered off. The solvent is evaporated and the crude product is vacuum distilled. Triethylamine and molecular sieves are added to the product and vacuum distilled at 0.1 torr between 25°C and 33°C to produce the desired product in very high purity (>99%) in about 75% yield.

[0214] DF1S 3 Thermal stability of MN:

[0215] Fig.10 Describes the LiPF 6 DF1S 3 Thermal stability of MN.DF1S 3 MN-LiPF 6 The electrolyte (ZP990-01) was exposed to temperatures ranging from 30°C to 150°C, and the gaseous and liquid decomposition products were analyzed by electron impact mass spectrometry (EI-MS) and nuclear magnetic resonance spectroscopy (NMR), respectively. 3 MN shows no significant gas and / or liquid phase decomposition up to 150°C.

[0216] Differential Scanning Calorimetry (DSC) Evaluation of Thermal Abuse Tolerance:

[0217] DSC measurements in the presence of delithiation cathode materials using F1S-based 3The results of the study were conducted on MN and carbonate electrolytes to evaluate potential thermal abuse tolerance effects that could translate into safety advantages in full cell format. Higher onset temperature, lower total heat output, and lower peak heat output are all effects that suggest improved thermal abuse behavior in full cell format.

[0218] Fig.11 Describes the LiPF 6 F1S with various carbonate co-solvents 3 The thermal stability of MN is comparable to that of LiPF 6 The cells containing the various electrolytes were charged to 4.25 V and then disassembled. The lithium nickel cobalt aluminum oxide (NCA) cathode was rinsed with ethylene carbonate and dried. Each sample containing 5 mg of active material and 2 mg of fresh electrolyte was hermetically sealed in a stainless steel DSC pan. A DSC scan at a rate of 2°C / min showed that the carbonate control electrolyte reacted at a much lower starting temperature than any of the silicone electrolyte blends. In addition, the electrolyte in which silicone replaced the EMC had a much lower peak heat output than the control electrolyte.

[0219] Preparation of electrolyte:

[0220] The blending of the electrolyte is completed in an argon glove box without moisture (<5ppm) and oxygen (<20ppm). All electrolyte components including solvents, salts and additives have been properly dried and stored in a glove box before blending. The solvent moisture is regularly monitored by Karl Fischer determination to ensure that the moisture level is maintained at <20ppm. Typically, the solvent is first weighed into a separate vial and mixed until uniform. 70% of the solvent is added to a volumetric flask. Slowly add lithium (or other) salts and stir until completely dissolved by a magnetic stirring bar. Subsequently, any other additives (i.e., VC, LiBOB) are slowly added and stirred until the solution is uniform. Remove the stirring bar and add a portion of the remaining solvent to complete the volume requirement. Put the stirring bar back into the volumetric flask and stir the electrolyte until uniform. After blending is completed, the electrolyte is dispensed into a dry vial or spare container for storage.

[0221] F1S 3 Performance of MN in lithium-ion batteries:

[0222] Fig.12 The discharge capacity at 30°C for cells containing various electrolyte solvents is described. In a 2032-type button cell assembly (such as in Fig.13Three different electrolyte solvents were tested in a series of cycles at different charge rates (C-rates) in a lithium-ion battery (assembly stacked in ). The three electrolyte solvents are: (1) a control EPA6 carbonate electrolyte (triangles) containing 1:1 (volume) ethylene carbonate (EC) and diethyl carbonate (DEC); (2) a control EPA6 carbonate electrolyte (triangles) containing 79% F1S 3 MN, 20% EC, 1M LiPF 6 and solid electrolyte interphase (SEI)-forming additives based on F1S 3 MN electrolyte (square); and (3) containing 79% F1S 3 M2, 20% EC, 1M LiPF 6 and SEI forming additives based on F1S 3 M2 electrolyte (circle). Fig.12 As shown in the F1S 3 The electrolyte of MN is equivalent to EPA6 at 4C charge rate.

[0223] Fig.14 Describes the Fig.12 Displayed in and for Fig.12 The discharge capacity of the battery with the same electrolyte at 55°C. The battery was assembled in the same manner and cycled at a C / 2 charge rate. Fig.14 As shown in the figure, compared with the carbonate control and the F1S-based 3 M2 electrolyte is compared with the F1S 3 The solvent of MN has improved cycling stability at 55 °C.

[0224] F1S 3 MN and DF1S 2 Performance of MN in double-layer capacitor batteries:

[0225] The symmetrical electric double layer capacitor (EDLC) is assembled as in Fig.15 A CR2032 button cell as described in . A glass fiber separator (AP40, Merck Millipore) was sandwiched between two AC (activated carbon) cloth electrodes, with 100 μl of electrolyte added to the separator. Tetraethylammonium tetrafluoroborate (TEA-BF 4 , Alfa Aesar, 99%) and tetrabutylphosphonium hexafluorophosphate (TBP-PF 6 , Sigma Aldrich, ≥99.0%) was used as the salt. Silicone solvent F1S 3 MN (99.4%) and DF1S 2MN (99.8%) was manufactured by Silatronix. Acetonitrile (AN, Sigma Aldrich, anhydrous, 99.8%) was used as a co-solvent.

[0226] Zorflex FM10 100% activated carbon (AC) cloth from Calgon Carbon is used as the two electrodes. FM10 has a 1000-2000m 2 / g surface area, 0.5 mm thickness and 120 g / m 2 The AC cloth was punched into 15 mm diameter disks and used directly as electrodes without any binder or conductive additives.

[0227] The performance of the EDLC cell was tested by cyclic voltammetry (CV) using a Biologic BMP300 constant potential instrument. The controlled temperature in the oven varied by ±0.1°C. The cyclic voltammetry (CV) response of the EDLC cell was performed at a scan rate of 10 mV / s between 0 V and 3 V. The normalized specific capacitance C was derived according to the following equation [1, 2]:

[0228]

[0229] Where i is the current, v is the scan rate, and m is the mass of an electrode.

[0230] Fig.16 Shows that it contains TEA-BF 4 Cyclic voltammogram of EDLC cell with OS electrolyte containing salt. The electrolyte ZX1193 contains DF1S dissolved in 70 vol% 2 MN and 1.0 M TEA-BF in 30 vol% acetonitrile 4 The electrolyte ZX1190 contains DF1S dissolved in a volume ratio of 60:40 2 MN and 0.8M TEA-BF in acetonitrile solvent 4 The EDLC cells with both electrolyte formulations showed regular and symmetrical characteristics with respect to the 0 horizontal axis, indicating the non-redox or inductive current nature of the cells.

[0231] Fig.17 Shown with TBP-PF 6 Cyclic voltammograms of EDLC cells with ZX1170 electrolyte and ZX1184 electrolyte. The electrolyte ZX1170 has a 3 1.2M TBP-PF in MN 6 The electrolyte ZX1184 has the ability to dissolve into DF1S 2 1.2M TBP-PF in MN 6Non-redox or inductive current properties can also be observed from EDLC cells with both electrolyte ZX1170 and ZX1184 formulations.

[0232] Synthesis of 1ND1N:

[0233] Scheme 16 describes the synthesis of 1ND1N. 1ND1N cannot be synthesized using sodium (Na), calcium oxide (CaO), or calcium hydride (CaH 2 )Chemical drying.

[0234]

[0235] Electrochemical stability of 1NDlN:

[0236] The molecular orbital diagrams (not shown) of 1ND1N and 1ND1 reveal that the energy difference between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of 1ND1N is 7.88 eV (LUMO=0.21 eV; HOMO=-7.88 eV) and the energy difference between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of 1ND1 is 8.36 eV (LUMO=1.63 eV; HOMO=-6.73 eV). 1ND1N has very good oxidation stability, but has lower reduction resistance than 1ND1.

[0237] Fig.18 The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1MLiPF 6 Or the oxidation stability of 1ND1N of 1M LiTFSI. The oxidation stability was tested at room temperature with platinum as the working electrode, lithium as the counter electrode, and Li / Li as the reference electrode. + , and the scanning speed is 10mV / s.

[0238] Fig.19 The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1MLiPF 6 Or the reduction stability of 1ND1N of 1M LiTFSI. The reduction stability was tested at room temperature with platinum as the working electrode, lithium as the counter electrode, and Li / Li as the reference electrode. + , and the scan rate was 10 mV / s. Two separate scans are shown for each electrolyte.

[0239] Fig. 20A and Fig. 20B For 1ND1N and 1M LiPF 6The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) relationship curve. Fig. 20A The first cycle is described. Fig. 20B The second cycle is described.

[0240] Fig.21A and Fig.21B The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship curve with 1M LiPF 6 F1S 3 Oxidative stability of MN or 1ND1N. Oxidative stability was tested at room temperature with platinum as the working electrode, lithium as the counter electrode, and Li / Li as the reference electrode. + , and the scanning speed is 10mV / s. Fig.21B Described in Fig.21A A close-up of the same data shown in F1S 3 MN-LiPF 6 The electrolyte has 1mA / cm at 7.3V 2 The current density of 1ND1N-LiPF 6 The electrolyte has 1 mA / cm at 7.2 V. 2 of current density.

[0241] Fig.22A and Fig. 22B The current density (mA / cm 2 ) and voltage (V, relative to Li / Li + ) describes the relationship between F1S with 1M LiTFSI 3 Oxidative stability of MN or 1ND1N. Oxidative stability was tested at room temperature with platinum as the working electrode, lithium as the counter electrode, and Li / Li as the reference electrode. + , and the scanning speed is 10mV / s. Fig. 22B Described in Fig.22A A close-up of the same data shown in F1S 3 MN-LiTFSI electrolyte has 1 mA / cm at 6.2 V 2 The current density of 1ND1N-LiTFSI electrolyte is 1 mA / cm at 6.5 V. 2 of current density.

[0242] Thermal stability of 1ND1N:

[0243] Fig.23The thermal stability of pure 1ND1N is described. 1ND1N was exposed to temperatures between 30°C and 189°C and the decomposition products were analyzed by mass spectrometry. 1ND1N showed no liquid or gas phase decomposition products up to 189°C. 1 H NMR showed about 5% decomposition.

[0244] Fig.24 Describes the LiPF 6 The thermal stability of 1ND1N. 6 The electrolyte was exposed to temperatures between 30°C and 150°C and the decomposition products were analyzed by mass spectrometry. The temperatures at which prominent peaks appeared are noted. 1ND1N showed gas phase decomposition ≥ 70°C, but no violent reactions were observed up to 150°C. Me 2 SiF 2 (81 m / z) (96 g / mol) and peaks at 52 / 53 m / z suspected to be acrylonitrile (53 g / mol). No 1,4-dioxane gas was observed at 150°C. 1 H NMR analysis showed 50.6% 1ND1N remaining at 125°C and 58% 1ND1N remaining at 150°C. At 125°C, 39.7% of the fluorinated product F1NM1N (compared to 2.3% in the unheated sample), 1.6% Me 2 SiF 2 (compared to 0% in the unheated sample) and 2.95% hydrolyzate (compared to 5.5% in the unheated sample). At 150°C, 41% of the fluorinated product F1NM1N (compared to 2.3% in the unheated sample), 1.7% Me 2 SiF 2 (compared to 0% in the unheated sample) and 5.0% hydrolysate (compared to 5.5% in the unheated sample).

[0245] In order to identify the heating of 1ND1N-LiPF at 125-150 °C 6 The peaks observed at 52 / 53 m / z when heated 1ND1N-LiPF 6 The mass spectral characteristics of the samples were compared with those of the National Institute of Standards and Technology (NIST) standards for 2-acrylonitrile and hydrogen cyanide. Fig.25A Describes how Fig.24 Close-up of mass spectral features from 24 to 30 m / z are depicted. Fig.25B Describes how Fig.24 Close-up of the mass spectral features depicted from 49 to 55 m / z. Fig.25A and Fig.25BThe temperature at which a prominent peak appears. Fig.25B The peaks at 51, 52, and 53 m / z in the NIST spectrum indicate the possible presence of acrylonitrile. The presence of HCN cannot be confirmed or confirmed due to the presence of peaks at 26 and 27 m / z in the NIST spectrum. Fig.25A The spectrum in shows a greater intensity of the peak at 26 m / z compared to 27 m / z, which supports the presence of acrylonitrile. However, the size of the peak at 27 m / z is larger than expected for acrylonitrile alone.

[0246] Fig.26 The thermal stability of 1ND1N with LiTFSI, vinylene carbonate (VC) and lithium bis(oxalato)borate (LiBOB) is described. 1ND1N-LiTFSI-VC-LiBOB was exposed to temperatures between 30°C and 185°C, and the decomposition products were analyzed by mass spectrometry. 1ND1N-LiTFSI-VC-LiBOB showed no gas-phase decomposition products up to 185°C. 1 H NMR showed that the hydrolysis increased from 3% (in the unheated sample) to 18.7% (after heating), which may be due to the delay before performing the NMR analysis.

[0247] Fig. 27 Describes the LiBF 4 The thermal stability of 1ND1N. 4 Exposure to temperatures between 30°C and 125°C and analysis of decomposition products by mass spectrometry. The temperatures at which prominent peaks appear are noted. Gas phase products are released at ≥30°C. As expected, Me 2 SiF 2 (81 m / z)(96 g / mol). No acrylonitrile was observed. 1 H NMR showed 3.7% hydrolyzate and 34.2% fluorinated product (3 groups of peaks). 19 F NMR shows that all F in the system is bonded to silicon. No BF is left. 4 There is not enough F to completely decompose 1ND1N (about 5M 1ND1N Vs. 4M F).

[0248] Although the mass spectrometry shows that in heated 1ND1N-LiBF 4 Acrylonitrile was not observed in the sample, but was observed in the unheated control (70 ppm). This indicates that 1ND1N has a high affinity for LiBF. 4 The case is unstable at room temperature. NMR analysis revealed that heating hardly increased the decomposition, as shown in the following table:

[0249]

[0250] Performance of 1ND1N in battery:

[0251] Fig.28 The discharge capacity of cells containing various electrolytes at various charge rates is described. The electrolyte solvents are: (1) 1ND1N; (2) 1ND1N with 20% ethylene carbonate (EC) cosolvent (1ND1N_EC); and (3) 1ND2 with 20% EC cosolvent (1ND2_EC). All formulations also contain SEI-forming additives and 1M LiPF 6 Salt. As in Fig.28 As shown in , 20% EC co-solvent improves the performance of 1ND1N. Compared to 1ND2, 1ND1N shows reduced performance at all charge rates with 20% EC co-solvent.

[0252] Fig.29 The discharge capacity of cells containing various other electrolyte solvents is described. The electrolyte solvents are: (1) with 20% EC co-solvent, 1M LiPF 6 1ND1N (1ND1N-EC-LiPF 6 ,exist Fig.29 (2) 1ND1N with 20% EC co-solvent, 1M LiTFSI and SEI forming additive (1ND1N-EC-LiTFSI, in Fig.29 and (3) with 20% EC co-solvent, 1M LiPF 6 1ND2(1ND2-EC-LiPF 6 ,exist Fig.29 1ND1N-EC-LiPF 6 The combination of 1ND1N-EC-LiTFSI and 1ND2-EC-LiPF 6 Combination of comparable performance.

[0253] Fig. 30A and Fig. 30B The charge rates of 1ND1N-LiPF 6The discharge capacity of the battery with electrolyte or 1ND1N-LiTFSI-based electrolyte. For each experiment, CR2032 button cells with Saft America (Cockeysville, MD) NCA cathode, graphite anode and 2500 separator from Celgard, LLC (Charlotte, NC) were used. The battery was charged to 4.1V using a constant current / constant voltage (CCCV) procedure at C / 5, C / 2, 1C or 2C charge rate. The battery was discharged to 3.0V per cycle at constant current at the same rate as the charge. Fig. 30A In the 1ND1N-LiPF 6 The electrolyte solution contains 1M LiPF 6 and 1ND1N (batch ZP780-01), and charging / discharging was performed at 30°C or 55°C. Fig. 30B In the 1ND1N-LiTFSI-based electrolyte solution, 1M LiTFSI and 1ND1N (batch ZT781-01) were used, and charging / discharging was performed at 30°C, 55°C, or 70°C. Fig. 30A and 30B As shown in Figure 2, the electrolyte based on 1ND1N-LiTFSI exhibits better performance than that based on 1ND1N-LiPF 6 The electrolyte has good rate capability.

[0254] Physical properties of OS solvent and electrolyte solutions:

[0255] Table 1 above shows selected organosilicon (OS) compounds (1S 3 MN、F1S 3 MN、F1S 3c MN、DF1S 3 MN、DF1S 2 MN and F1S 3 Table 2 shows the physical properties of pure 1ND2, 1ND1, 1ND1NF1S 3 MN、DPF1S 3 MN、F1S 3 MC, F1S 3 ME, F1S 3 MA, F1S 3 MS, 1NMS, F1S 3 M2 and F1S 3c Physical properties of MN and various electrolyte compositions containing them. In both tables, the unit of conductivity is mS / cm, the unit of viscosity is cP, and the flash point is in degrees Celsius.

[0256] In CDCl3 1ND1N, 1ND1N, DF1S obtained from 2 MN、DF1S 3 MN、F1S 3c MN and 1S 3 The proton of MN ( 1 H) NMR spectra are provided at Figure 31-36 For the selected compounds containing fluorine atoms, 19 F-NMR data in CDCl 3 and DMSO- d6 The results are as follows:

[0257] In CDCl 3 In 19 F-NMR

[0258] F1S 3 MN -162.3ppm, 1 J( 19 F, 29 Si)=280Hz

[0259] isoF1S 3 MN -166.6ppm, 1 J( 19 F, 29 Si)=284Hz

[0260] DF1S 3 MN -135.3ppm, 1 J( 19 F, 29 Si)=296Hz

[0261] TF1S 3 MN -136.8ppm, 1 J( 19 F, 29 Si)=280Hz

[0262] DF1S 2 MN -135.2ppm, 1 J( 19 F, 29 Si)=296Hz

[0263] In DMSO-d 6 In 19 F-NMR

[0264] F1S 3 MN -159.2ppm, 1 J( 19 F, 29 Si)=279Hz

[0265] Thermal stability of OS electrolyte solution:

[0266] Fig.37 and Fig.38 Describes a 1MLiPF 6 F1S 3 MC, F1S 3c MN, 1S 3 DND 2 MN, TF1S 2 MN and TF1S 3 Gas-phase decomposition of MN. Each electrolyte was exposed to temperatures between 30°C and 175°C (60 minutes in each step), and the gaseous and liquid decomposition products were analyzed by electron impact mass spectrometry (EI-MS) and nuclear magnetic resonance spectroscopy (NMR), respectively. No significant gas-phase and / or liquid-phase decomposition was observed up to 175°C.

[0267] in conclusion:

[0268] F1S 3 Both MN and 1ND1N are suitable for use as electrolyte solvents in lithium-ion batteries. 3 MN and DF1S 2 MN acts as the electrolyte solvent in EDLC devices. 3 MN showed high thermal stability for all salts tested (by 1 H-NMR measurement). 3 MN with LiPF 6 F1S showed the highest thermal stability (175°C) among all OS, and no decomposition was observed. 3 MN as pure solvent and LiBF 4 Together with LiTFSI, gaseous products are produced. These gaseous products can be attributed to the low level of F1S 3 MN evaporation. F1S 3 MN Display and F1S 3 Increased voltage stability compared to M2 (higher oxidation potential in a wide window). At charge rates up to 4C, F1S 3 MN still provides comparable performance to EPA6. LiBOB in F1S 3 LiBOB has limited solubility in MN without cosolvent (<0.03 M), but with the use of cosolvent (i.e., 20% EC), LiBOB solubility improves (>0.1 M). 3 The decomposition product of MN is Me 2 SiF 2 and MeSiF 3 , both of which are gases.

[0269] 1ND1N as pure solvent or in combination with LiTFSI electrolyte also showed no gas phase decomposition up to 185-190 °C. The combination of 1ND1N with LiTFSI electrolyte showed promising results up to 70 °C and higher. 6 The 1ND1N ratio of LiPF 6 1ND1 or 1ND2 is more thermally stable. It forms acrylonitrile above 125°C. Like other spacer-free compounds, 1ND1N reacts with LiBF at room temperature. 4 reaction. However, there is not enough F to completely decompose 1ND1N, and it does not form acrylonitrile. The rate performance of 1ND1N is slightly lower than that of 1ND2.

[0270] F1S 3 MN、DPF1S 3 MN and F1S 3 MC is suitable for use as electrolyte solvent in lithium-ion batteries. 3 MC, F1S 3c MN, 1S 3 DN、DF1S 2 MN, TF1S 2 MN and TF1S 3 MN and LiPF 6 Thermally stable (175°C), no decomposition was observed.

Claims

1. A compound selected from: (R) 4-a -Si-(Sp-Y) a -Z b (Formula I) in: "a" is an integer from 1 to 4; "b" is an integer from 0 to (3xa); When "b" = 0, "Z" does not exist, otherwise "Z" is selected from "R" and wherein "R" is independently selected from halogen; 1-6 A straight or branched alkyl, alkenyl or alkynyl group; and C 1-6 a straight-chain or branched haloalkyl, haloalkenyl or haloalkynyl group; In formula I and II, "Sp" is independently selected from C 1-15 Straight or branched alkylene and C 1-15 a linear or branched haloalkylene group; and "Y" in Formula I are each independently selected from organic polar groups.

2. The compound of claim 1, wherein each "Y" is independently an organic polar group selected from the following: The bent bond represents C 2-6 Alkylene bridging moiety.

3. The compound of claim 2, wherein each "Y" is independently an organic polar group selected from the following:

4. The compound of claim 3, wherein "R" is independently selected from fluorine and C 1-6 a linear or branched fluoroalkyl, fluoroalkenyl or fluoroalkynyl group; and In formula I and II, "Sp" is independently selected from C 1-15 A linear or branched fluoroalkylene group.

5. The compound of any one of claims 1 to 4, wherein "a" is 1 and "b" is 0-3.

6. The compound of claim 5, wherein "b" is 1 and "Z" is "-R".

7. The compound of claim 5, wherein at least one "R" is fluorine and "Sp" is each independently selected from C 1-6 Straight chain alkylene and C 1-6 Straight chain fluoroalkylene.

8. The compound of any one of claims 1 to 4, wherein "a" is 2 and "b" is 0-6.

9. The compound of claim 7, wherein "b" is 1 and "Z" is "R".

10. The compound of claim 7, wherein at least one "R" is fluorine and "Sp" is each independently selected from C 1-6 Straight chain alkylene.

11. The compound of any one of claims 1 to 4, wherein "a" is 3 and "b" is 0-9.

12. The compound of claim 11, wherein "b" is 1 and "Z" is "R".

13. The compound of claim 11, wherein at least one "R" is fluorine and "Sp" is each independently selected from C 1-6 Straight chain alkylene.

14. The compound of any one of claims 1 to 4, wherein "a" is 4 and "b" is 0-12.

15. The compound of claim 14, wherein "b" is 1 and "Z" is "R".

16. The compound of claim 14, wherein at least one "R" is fluorine and each "Sp" is independently selected from C 1-6 Straight chain alkylene.

17. The compound of any one of claims 1 to 4, wherein at least one "R" is fluoro.

18. An electrolyte composition comprising the compound according to any one of claims 1 to 4 and a salt.

19. The electrolyte composition of claim 18, wherein the salt is a lithium-containing salt.

20. An electrochemical device comprising the electrolyte composition according to claim 18.